Thermal analysis of a three-dimensional breast model with embedded tumour using the transmission line matrix (TLM) method - Amri, A.; Saidane, A.; Pulko, S. (Computers in biology and medicine, 2011)
Breast thermography is a non-invasive tool for early detection of breast cancer. It was subject for many years to some controversial issues regarding its efficiency. Advances in infrared camera technology and progress in image processing systems had brought thermal breast imaging back as a valid tool for mammography. Numerical modelling of heat transfer within a woman breast is being an attractive tool that may reveal the conditions under which tumours can be detected in a thermogram. The aim of this work is to use the transmission line matrix (TLM) to model a regular three-dimensional breast with embedded tumour and analyse sensitivity parameters.